Molecular genetics and racial disparities of uterine leiomyomas - Othman, Essam El-Din R. (2008)
Uterine leiomyomas (ULMs) are benign oestrogen-dependent tumours of the myometrium. They are the most common tumours of the female genital tract, affecting around 77% of the female population. ULMs are more common in Black women than White women. These tumours tend to develop earlier and be more numerous, larger in size and more symptomatic in Black women than other ethnic groups. The molecular mechanism underlying this ethnic disparity is not fully understood. Polymorphism of genes involved in oestrogen synthesis and/or metabolism (COMT, CYP17), variation in the expression levels or function of oestrogen and progesterone receptors or retinoic acid nuclear receptors (retinoid acid receptor-α, retinoid X receptor-α), or aberrant expression of micro-RNAs are some of the molecular mechanisms that may be involved.